The association between labor epidural analgesia and early-onset postpartum hypertension among parturients with hypertensive disorders of pregnancy: A retrospective cohort study - Yongle Li; Jiteng Hu; Jiao Duan; Junjian Wen; Jianxiong Huang; Jie Shen; Zurong Hu; Zaisheng Qin (PLoS ONE, 2025)
Background This study aimed to investigate the association of different durations of labor epidural analgesia (LEA) on early-onset postpartum hypertension (PPHTN) among parturients with hypertensive disorders of pregnancy (HDP). Methods We conducted a retrospective cohort study in which patients who were diagnosed with hypertensive disorders of pregnancy between 2018 and 2023. The parturients who received LEA were divided into three groups based on the tertiles of LEA duration: the short-duration group (< 175 minutes), the medium-duration group (175–324 minutes), and the long-duration group (≥ 325 minutes), while parturients who did not receive LEA forming the control group. The primary outcome was early-onset PPTHN, defined as the occurrence of at least one blood pressure measurement meeting hypertensive criteria within 2 days following delivery. Three multivariate logistic regression models was employed to explore the association between the duration of LEA exposure and early-onset PPHTN. Four sets of sensitivity analyses were conducted to assess the robustness of the analysis. Results In the study cohort of 1,316 parturients, 36.0% (n = 474) were diagnosed with early-onset PPHTN. Compared with those who did not receive LEA, parturients who received long-exposure LEA had significantly lower incidences of early-onset PPHTN (29.5% vs 41.7%, P < 0.05). Univariate survival analysis demonstrated that long-duration LEA was associated with a lower risk of PPHTN during hospitalization (HR = 0.75, 95% CI: 0.59–0.95, P < 0.05). All three models showed long-exposure LEA exposure was associated with a reduced incidence of early-onset PPHTN among parturients with HDP. Consistent results were observed in the sensitivity analysis conducted among parturients with documented antepartum hypertension who received multiple antihypertensive medications during pregnancy, as well as among those who did not require antihypertensive therapy during the postpartum period. However, this association did not reach statistical significance when the follow-up period was extended to five days postpartum, or in subgroups of parturients with advanced maternal age, obesity, or PE. Conclusion A longer duration of LEA was associated with a reduced risk of early-onset PPHTN among women with HDP. However, this association did not reach statistical significance in subgroups of parturients with advanced maternal age, obesity, or PE.